Separation of C5/C6 isomerate fractions in a mixed/layered bed of BETA/5A zeolites - Brântuas, Pedro (2018)
The combustion quality of gasoline is measured by the research octane number (RON). When RON is high, the combustion occurs like a smooth explosion instead of a detonation and the performances of the motor are improved. Cracking, alkylation, isomerization and other process can be used to increase the RON of gasoline to about 90. The light straight-run (LSR) naphtha fraction produced by fractional distillation is one of the feedstocks used to produce gasoline. Its major constituents include C5 and C6 normal paraffins which have relatively low RON compared to their branched isomers. Therefore, octane upgrading commonly uses isomerization to rearrange the structure of the linear paraffins into branched components. The product stream from an isomerization reactor consists of hexane isomers: 2,2-dimethylbutane (22DMB), 2,3-dimethylbutane (23DMB), 2-methylpetane (2MP), 3-methylpentane (3MP), n-hexane (nHEX), as well as pentane isomers: iso-pentane (iPEN) and n-pentane (nPEN). Zeolite 5A is used to separate the linear isomers (nHEX and nPEN) from the branched isomers, returning them to the isomerization reactor for further processing, while the other isomers are retained as product. Denayer et al. [1] found that pentane and hexane isomers might be separated by chromatography according to their degree of branching using columns of zeolite beta, and some years before Huddersman and Klimczyk [2,3] indicated that zeolite beta in cation form (H, Ba) is an effective adsorbent for the separation of branched hexane isomers. Therefore, using both zeolites together should allow for a better separation of the high RON isomers (22DMB, 23DMB and iPEN) from the remaining isomers, specially the low RON isomers (nPEN and nHEX). Thus, four different adsorber bed configurations were studied: zeolite beta; a layered bed of zeolite 5A followed by zeolite beta; a layered bed first with zeolite beta followed by zeolite 5A; and, a mixed bed of both zeolites with the objective of analyzing the effect of each configuration on the adsorption and separation of alkane isomers.